An Ir(III) Complex Photosensitizer With Strong Visible Light Absorption for Photocatalytic CO2 Reduction - Kuramochi, Yusuke; Ishitani, Osamu (Frontiers in Chemistry, 2019)
A cyclometalated iridium(III) complex having 2-(pyren-1-yl)-4-methylquinoline ligands (Ir(pyr)) has a strong absorption band in the visible region (ε444nm = 67,000 M−1cm−1), but does not act as a photosensitizer for photochemical reduction reactions in the presence of triethylamine as the electron donor. Here, 1,3-dimethyl-2-(o-hydroxyphenyl)-2,3-dihydro-1H-benzo[d]imidazole (BI(OH)H) was used instead of the amine, demonstrating that BI(OH)H efficiently quenched the excited state of Ir(pyr) and can undergo the photochemical carbon dioxide (CO2) reduction catalyzed by trans(Cl)-Ru(dmb)(CO)2Cl2 (dmb = 4,4’-dimethyl-2,2’-bipyridine, Ru) to produce formate as the main product. We also synthesized a binuclear complex combining Ir(pyr) and Ru via an ethylene bridge and investigated its photochemical CO2 reduction activity in the presence of BI(OH)H